Guidelines for improving the loyalty of Chinese tourists in Thailand - HAN, PEIJUN (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
This thesis is intended to 1. Study the factors that influence the way to develop the loyalty of Chinese tourists in Thailand and 2. Find ways to improve the loyalty of Chinese tourists in Thailand. The example used in this research is 400 Chinese tourists who travel repeatedly in Thailand. Key informant are 5 Chinese tour operators in Thailand. Inquire about the development guidelines for repeat tourism of Chinese tourists in Thailand. By bringing the results from quantitative research into the study before conducting an in-depth interview. Data collection tools. Namely, questionnaires, statistics used in data analysis, including percentage, mean, standard deviation, One-way analysis of variance and multiple regression analysis. The research found that 1. Marketing mix Affecting the loyalty of Chinese tourists in Thailand. The results showed that the marketing mix of products and marketing promotion had statistically significant results. With a coefficient of 0.66 and 0.44. The equation has 27 percent predictive power and can be written as an equation as follows. Y = 2.42 + 0.66 Products * +0.34 Price +0.19 Place +0.44 Promotion* 2. Guidelines for improving the loyalty of Chinese tourists in Thailand can be concluded that the development of the loyalty of Chinese tourists in Thailand Must be born from understanding And good relationships. In the field of telecommunications services Security Most Chinese tourists are already ready to come to Thailand. Development in the facility and safety point Will help build confidence And the impression of tourism And telling impressions to relatives And the next friend Article history : Received 28 April 2019 Revised 9 June 2019 Accepted 11 June 2019 SIMILARITY INDEX = 3.93 %